The New Microfinance Handbook : A Financial Market System Perspective - Ledgerwood, Joanna (Washington, DC: World Bank, 2013)
The new microfinance handbook provides a primer on financial services for the poor. It is written for a wide audience, including practitioners, facilitators, policy makers, regulators, investors, and donors working to improve the financial system, but who are relatively new to the sector. It will also be useful for telecommunication companies and other support service providers, students and academics, and consultants and trainers. Although this book is in part an update of the original handbook, the growth of the sector and the complexity of the financial market system have led to a perspective much broader than the previous 'financial and institutional perspective.' As a result, additional chapters have been added to address issues more relevant than when the original handbook was written. To reflect this complexity, the author invited a number of experts to write many of the new chapters. In addition, given that this book does not go into as much detail as the previous book did, a list of key resources at the end of each chapter provides readers additional information on specific topics. Finally, although the title still uses the term microfinance, the book very much addresses the wider financial ecosystem, moving beyond the traditional meaning of microfinance to inclusive financial systems.